(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Recently, one can observe the growing interest of linguistics in the problem of emotions in language. Many scientific disciplines are engaged in the study of emotions and the sensory domain of a person. From the point of view of linguistics, the study of emotivity corresponds to the modern anthropocentric approach to language learning, which puts a person with his experiences, feelings and needs at the center of analysis. The article identifies ways to implement the category of emotivity.